2019
DOI: 10.2217/pme-2018-0141
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Effectiveness of BRCA1/2 Mutation Profiling to Target Olaparib Use in Patients with Metastatic Breast Cancer

Abstract: Aim: Olaparib monotherapy improves progression-free survival in patients with metastatic breast cancer and BRCA1/2 mutations. We evaluated the cost–effectiveness of BRCA1/2 mutation profiling to target olaparib use. Methods: A Markov cohort model was generated to compare the 5-year cost–effectiveness of BRCA1/2 mutation profiling to target olaparib use. Results: The incremental cost–effectiveness ratio of BRCA1/2 mutation profiling plus olaparib monotherapy was JPY14,677,259/quality-adjusted life year (QALY) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Recent studies have suggested that population-based genetic testing is more cost-effective than a strategy based on clinical criteria and family history [ 28 , 29 ]. Although a recent Japanese study of patients with MBC suggested that BRCA1/2 profiling combined with olaparib treatment provided a minimal incremental benefit versus standard chemotherapy alone [ 30 ], other studies have demonstrated cost-effectiveness of routine/mainstream genetic testing for all patients diagnosed with breast cancer to guide subsequent personalized therapy [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that population-based genetic testing is more cost-effective than a strategy based on clinical criteria and family history [ 28 , 29 ]. Although a recent Japanese study of patients with MBC suggested that BRCA1/2 profiling combined with olaparib treatment provided a minimal incremental benefit versus standard chemotherapy alone [ 30 ], other studies have demonstrated cost-effectiveness of routine/mainstream genetic testing for all patients diagnosed with breast cancer to guide subsequent personalized therapy [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies investigated the cost-effectiveness of PARP inhibitor versus standard chemotherapies in these patients, and both deemed the former not cost-effective. Saito’s group in Japan compared the strategy of olaparib monotherapy after positive BRCA mutation profiling to the use of capecitabine, eribulin, or vinorelbine without testing and discovered that the former costs $131,047 per QALY, which was hardly cost-effective at the WTP threshold of $89,286 ( Saito et al, 2019 ). Regarding talazoparib, consistent findings were presented in a Spanish study by Lima and others, who obtained ICERs slightly above $280,000 per QALY in two scenarios compared with capecitabine or eribulin, which were ten-fold higher than the threshold of $23,945 ( Olry de Labry Lima et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…ICERs were less sensitive to the costs of chemotherapies, hospital care, general adverse event management, and molecular testing. As for clinical estimates, models were more sensitive to the hazard ratios of PFS or the ratios used to project overall survival, time-receiving maintenance treatment, and utility values at progressive disease state ( Smith et al, 2015 ; Zhong et al, 2018 ; Guy et al, 2019 ; Saito et al, 2019 ; Armeni et al, 2020 ; Barrington et al, 2020 ; Su et al, 2020 ; Wu and Shi 2020 ; Leung et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to pancreatic cancer, olaparib was also not cost-effective when used in patients with ovarian cancer in the USA or breast cancer in Japan. 17,18 In 2015, Smith built decision analysis models and found that the ICER was $258,864 per progression-free life-year saved for olaparib maintenance therapy in ovarian cancer patients with a BRCA mutation. Drug cost had the highest impact on the ICER; to achieve an ICER of less than $50,000, the cost of olaparib would have had to decrease to $2500 or less per month.…”
Section: Discussionmentioning
confidence: 99%